Comparison of Tungsten Carbide and Arkansas Stone For Adhesive Removal On Enamel Surface After Debonding Procedure - Noviyanti Putri, Aditya Kartika; Hamid, Thalca; Triwardhani, Ari (Faculty of Dental Medicine Universitas Airlangga, 2018)
Background: Debonding aims to remove orthodontic appliances from the patient's teeth and cleanse all residual adhesive material on the surface of the tooth to restore surface conditions such as before orthodontic treatment. Damage may occur after debonding process. Removal of the remaining adhesive material has a major effect on the enamel surface conditions, the researcher wants to know the effect of cleaning adhesive material using Tungsten carbide 12 flute burs, Arkansas stone bur on the enamel surface Purpose: To determine the effect of cleaning the remaining adhesive material using Tungsten carbide 12 flute burs and Arkansas stone bur Against the Surface of the Enamel. Method: This study was experimental laboratory (in vitro study) with 4 groups division, first control group was tooth before bracket was installed, group 2 was done debonding without cleaning of residual adhesive, group 3 was done adhesive cleansing with Arkansas stone and group 4 was done adhesive cleaning with tungsten carbide 12-flutted Result: Showing that the use of 12-flutted tungsten carbide was able to clean enamel surfaces with the most delicate results and did not cause cracks or cracks on enamel surface Conclusions: The best method to clean the remaining adhesive is using 12-flutted tungsten carbide bur using contra angle high speed and with adequate water flow and sprays to prevent increasing of temperature that damage dental pup.